Double Potential Pulse Chronocoulometry for Detection of Plasma Membrane Cholesterol Efflux at Disk Platinum Microelectrodes - West, Richard H. (J Electrochem Soc, 2014)
A double potential pulse scheme is reported for observation of cholesterol efflux from the plasma membrane of a single neuron cell. Capillary Pt disk microelectrodes having a thin glass insulator allow the 10 μm diameter electrode and cell to be viewed under optical magnification. The electrode, covalently functionalized with cholesterol oxidase, is positioned in contact with the cell surface resulting in enzyme catalyzed cholesterol oxidation and efflux of cholesterol from the plasma membrane at the electrode contact site. Enzymatically generated hydrogen peroxide accumulates at the electrode/cell interface during a 5 s hold-time and is oxidized during application of a potential pulse. A second, replicate potential pulse is applied 0.5 s after the first potential pulse to gauge background charge prior to significant accumulation of hydrogen peroxide. The difference in charge passed between the first and second potential pulse provides a measure of hydrogen peroxide generated by the enzyme and is an indication of the cholesterol efflux. Control experiments for bare Pt microelectrodes in contact with the cell plasma membrane show difference charge signals in the range of about 7–10 pC. Enzyme-modified electrodes in contact with the plasma membrane show signals in the range of 16–26 pC.